Implementation of a low cost ac-dc converter for high and low power applications - Ilambirai, R. C.; Sekhar Dash, Subhransu; Rayaguru, N K (International Journal of Engineering and Technology, 2017)
This paper proposes an ac-dc converter that gives multiple outputs capable of feeding both high and low power applications. The input ac supply is converted to dc by a diode bridge rectifier, filtered and fed to a modified multiport converter (MPC). This paper focuses on the design of the modified multiport converter that has a cascaded combination of zeta and a buck converter. This is designed as a single input and multiple output converter (SIMO) structure which can operate two loads, one with a high power and other with a low power application, depending on the time instant. The need for opting a multiport converter, reduces the number of switches utilized, thereby reducing the switching losses in the circuit. The zeta in the MPC boosts the input voltage and the buck converter reduces the input voltage and is accordingly fed to the need of the load. The design of the components have been analysed through steady state. MATLAB Simulink has been used to simulate the converter circuit and the varied outputs of the zeta and buck modes are compared. A hardware prototype of the ac-dc converter has been implemented and their results have been shown.